Recent developments of HDAC inhibitors: Emerging indications and novel molecules - Bondarev, Andrey D.; Attwood, Misty M.; Jonsson, Jörgen; Chubarev, Vladimir N.; Tarasov, Vadim V.; Schiöth, Helgi B. (British journal of clinical pharmacology, 2021)
The histone deacetylase (HDAC) enzymes, a class of epigenetic regulators, are historically well established as attractive therapeutic targets. During investigation of trends within clinical trials, we have identified a high number of clinical trials involving HDAC inhibitors, prompting us to further evaluate the current status of this class of therapeutic agents. In total, we have identified 32 agents with HDAC‐inhibiting properties, of which 29 were found to interact with the HDAC enzymes as their primary therapeutic target. In this review, we provide an overview of the clinical drug development highlighting the recent advances and provide analysis of specific trials and, where applicable, chemical structures. We found haematologic neoplasms continue to represent the majority of clinical indications for this class of drugs; however, it is clear that there is an ongoing trend towards diversification. Therapies for non‐oncology indications including HIV infection, muscular dystrophies, inflammatory diseases as well as neurodegenerative diseases such as Alzheimer's disease, frontotemporal dementia and Friedreich's ataxia are achieving promising clinical progress. Combinatory regimens are proving to be useful to improve responsiveness among FDA‐approved agents; however, it often results in increased treatment‐related toxicities. This analysis suggests that the indication field is broadening through a high number of clinical trials while several fields of preclinical development are also promising.